1999
DOI: 10.1111/j.1365-2621.1999.tb15061.x
|View full text |Cite
|
Sign up to set email alerts
|

Color and Pigment Stability of Red Radish and Red‐Fleshed Potato Anthocyanins in Juice Model Systems

Abstract: Color and pigment stability of model juices (pH 3.5) were evaluated during 65 wk of storage at 28C and 258C in the dark. Two acylated pelargonidin-based anthocyanins, red-fleshed potatoes (Solanum tuberosum) and red radishes (Raphanus sativus), and 2 extraction methods, C-18 resin and juice processing, were used and compared to FD&C Red #40. Color (CIELch) and pigment degradation depended on storage temperature, anthocyanin structure and extraction method, with chemically extracted radish anthocyanins showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(105 citation statements)
references
References 34 publications
(52 reference statements)
10
87
1
5
Order By: Relevance
“…Similar increasing trends of L ⁄ and H°were also observed in non-thermally treated solutions containing anthocyanins stored at 6, 25, and 40°C for up to 22 days (West & Mauer, 2013) and in ultrasonically treated berry juices (lingonberry, cranberry, and strawberry) stored at room temperature for 103 days (Rein & Heinonen, 2004). Rodríguez-Saona, Giusti, and Wrolstad (1999) reported an increase in L ⁄ of 10 units during the storage of radish anthocyanin extract for 42 weeks, radish juice for 27 weeks, and potato juice and potato anthocyanin extract for 20 weeks, respectively, stored at 25°C. In our study, the increases in L ⁄ of the anthocyanin aqueous solutions stored at 25°C were observed to occur faster, considering the shorter storage time (21 days), with an increase of about 6, 5, 8, 29, 39 units for control, anthocyanin aqueous solutions thermally treated at 90, 100, 120, and 140°C (30 s), respectively.…”
Section: Changes In Color During Storagesupporting
confidence: 74%
“…Similar increasing trends of L ⁄ and H°were also observed in non-thermally treated solutions containing anthocyanins stored at 6, 25, and 40°C for up to 22 days (West & Mauer, 2013) and in ultrasonically treated berry juices (lingonberry, cranberry, and strawberry) stored at room temperature for 103 days (Rein & Heinonen, 2004). Rodríguez-Saona, Giusti, and Wrolstad (1999) reported an increase in L ⁄ of 10 units during the storage of radish anthocyanin extract for 42 weeks, radish juice for 27 weeks, and potato juice and potato anthocyanin extract for 20 weeks, respectively, stored at 25°C. In our study, the increases in L ⁄ of the anthocyanin aqueous solutions stored at 25°C were observed to occur faster, considering the shorter storage time (21 days), with an increase of about 6, 5, 8, 29, 39 units for control, anthocyanin aqueous solutions thermally treated at 90, 100, 120, and 140°C (30 s), respectively.…”
Section: Changes In Color During Storagesupporting
confidence: 74%
“…1). Concerning the diminution of the anthocyanins content recorded in 90 and 180-days liqueurs, it is widely accepted that their stability could be reduced by a number of factors such as pH, temperature, copigments, self-association, and the presence of metallic ions and sugars, among others (Rodríguez-Saona, Glusti, & Wrolstad, 1999). Instead, it has been shown that anthocyanins pass from fruits to liqueurs during the first 30-60 days (Gironés-Vilaplana, Mena, García-Viguera, and Moreno, 2012), while in the present work the specific characteristics of grape stems matrix seem to allow a faster leaching in comparison with fruit liqueurs.…”
Section: (Poly)phenolic Content In Prepared Liqueursmentioning
confidence: 99%
“…The total ascorbic acid (vit-C) content was determined using the method modified by Hashimoto and Yamafuji (2001). The total anthocyanin contents of the hydrophilic extracts were measured by the pH differential method (Rodriguez-Saona et al 1999). The PAL activity in the crude enzyme extracts was assayed using the method as described by Zucker (1965) and expressed as nmol cinnamic acid yield.…”
Section: Measurement Of Physiological and Biochemical Parametersmentioning
confidence: 99%